Substituição parcial do farelo de algodão por uréia em rações à base de feno de matapasto (Cassia tora, L.) e maniva de mandioca (Manihot utilissima, Pohl.). - Lima, Manoel Messias Muniz (1994)
The present research was carried out at the Digestibility Sector of the Department of Zootechny of the Center of Agricultural Sciences of the Federal University of Ceará, in Fortaleza, Ceará, aiming at evaluating the nourishing value of cattle feed with a basis of coffeeweed hay (Cassia tora, L.) and manioc stems (Manihot utilissima, Pohl.), and a supplement of urea in partial substitution for cotton bran. TweIve ovine specimens of the Morada Nova breed, variety White, adult, castrated and tailed, alI in good health conditions, were observed over a period of 35 days, 21 of which comprised the period of observation and were followed by a seven-day period of adjustment and another seven days for sample collecting. The diets were basically made up of manioc stems (30%), blackstrap (2%), calcium carbonate (0.8%), bone fiour (0.5%), sulphur (0.1%) and a blend of minerals (0.6%). Other ingredients respectively constituted diets A, B, C and D, as follows: cotton bran (26.0; 19.0; 12.0 and 5.0%), corn bran (10.0; 16.50; 23.0 and 29.5%) and urea (0.0; 0.5; 1.0 and 1.5% ). Variation analysis followed an experimental deIineation entirely case-based, with four treatments (diets) and three repetitions (ovine specimens). As far as nourishing parameters are concerned, the following were evaluated: spontaneous ingestion of natural matter and dried matter, and apparent digestibility of nourishing ingredients. The analysis of the data variation did not reveal any significant difference (P> 0.05) between diets as concerns the ingestion of natural matter and dried matter, even though ingestion did decrease as the leveI of urea reached 1.5%. The apparent digestibility data for dried matter, organic matter and raw energy did not show statistically reIevant differences between diets (P > 0.05), but the highest digestibility rates for these nourishing ingredients were obtained with the level of urea at 1.0%. The digestibility rate for fiber in neutral detergent, which constitutes the carbohydrate portion of the cellular contents, and is therefore easily digestible, did present a significant difference (P < 0.5) between diets with 0.0 and 1.0% urea. The apparent digestibility rates of raw protein increased w ith the levels of urea, and no statistically relevant differences (P > 0.05) were observed between diets with 1.0 and 1.5% urea. The components of the fibrous portions of the experimental diets (raw fiber, cellulose and fiber in acid detergent) presented statistically relevant differences (P < 0.05) between diets, higher rates of digestibility for these substances being observed when the leveI of urea reached 1.0 %.